Combined iDISCO and CUBIC tissue clearing and lightsheet microscopy for in toto analysis of the adult mouse ovary†. Issue 5 (24th January 2020) - McKey, Jennifer; Cameron, Lisa A; Lewis, Devon; Batchvarov, Iordan S; Capel, Blanche
Abstract: At any given time, the ovary contains a number of follicles in distinct growth stages, each with a set of identifying characteristics. Although follicle counting and staging using histological stains on paraffin-embedded ovary sections has been the gold standard in assessing ovarian health in fertility studies, the final counts rely on extrapolation factors that diverge greatly among studies. These methods also limit our ability to investigate spatial aspects of ovary organization. Recent advances in optical tissue clearing and lightsheet microscopy have permitted comprehensive analysis of intact tissues. In this study, we set out to determine the best clearing and imaging methods to generate 3D images of the complete adult mouse ovary that could be used for accurate assessments of ovarian follicles. We found that a combination of iDISCO and CUBIC was the best method to clear the immunostained ovary. Using lightsheet microscopy, we generated 3D images of the intact ovary and performed qualitative assessments of follicles at all stages of development. This study is an important step toward developing quantitative computational models that allow rapid and accurate assessments of growing and quiescent primordial follicles, and to investigate the integrity of extrinsic ovarian components including vascular and neuronal networks. Abstract : The combination of iDISCO and CUBIC tissue clearing methods allows in toto imaging of the ovarian follicle composition and extrinsic vascular and neuronal networks.